Diakonia: Today's Task - Hase, Hans Christoph von (Scottish journal of theology, 1967)
In spite of all the gaps in the Church's tradition, it has become clear how strong the continuity of creed and liturgy, even of office and law, has been through the centuries.2 The history of diakonia, however, presents a strangely divergent picture. Admittedly Christ's command of love has been proclaimed in an unbroken line, but the actual loving deeds of the Church, their forms and institutions, show a striking discontinuity. Diakonia will break out with charismatic vigour and direct men for centuries to new ways of service, then it suddenly collapses and only a few venerable ruins remain. This has little to do with favourable or unfavourable political conditions. Diakonia never blossomed more richly than in the times of persecution under a Decius or Diocletian; and the Church was never relieved of more service than under Christian rulers through the secularisation of the West in recent centuries. Either it proves itself man's true help in time of need, or it dies a quick death (cf. Matt. 5.13).